2016
DOI: 10.11157/anzswj-vol28iss1id112
|View full text |Cite
|
Sign up to set email alerts
|

Comparing public perceptions of social work and social workers’ expectations of the public view

Abstract: INTRODUCTION: Previous studies have explored public perception of social work and social workers. There is little written about what social workers think about how they, and the profession of social work, are viewed by the public. This article explores the views of a sample of social workers in Aotearoa New Zealand about their beliefs around the public perception of social work and social workers.AIMS: This article aims to explore social worker views on the public perception of social work, and then compares t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 8 publications
(19 reference statements)
0
15
0
3
Order By: Relevance
“…Other negative comments social workers expected the public to use to describe them included "do gooders" and "interfering/busy body." Earlier research by Davidson and King (2005) also supports the findings from Staniforth et al (2016). Davidson and King (2005) discovered that twice as many people were likely to have positive views of social work than negative ones.…”
Section: Original Articlementioning
confidence: 65%
See 1 more Smart Citation
“…Other negative comments social workers expected the public to use to describe them included "do gooders" and "interfering/busy body." Earlier research by Davidson and King (2005) also supports the findings from Staniforth et al (2016). Davidson and King (2005) discovered that twice as many people were likely to have positive views of social work than negative ones.…”
Section: Original Articlementioning
confidence: 65%
“…These views were then compared with those of the 386 members of the public from Staniforth, Fouché, and Beddoe's 2014 study. Staniforth et al (2016) found that members of the public actually perceived social work in a more positive light than social workers believe they do. In the 2014 study, members of the public were asked to suggest three words that define social workers; most often people said "helper," "meets specific need" or "children/youth help."…”
Section: Original Articlementioning
confidence: 96%
“…Зарубіжні науковці, досліджуючи імідж соціальних працівників і сприйняття громадськістю їх як фахівців із соціальної роботи дійшли висновку, що, насамперед, фахівці повинні інформувати суспільство про цілі своєї діяльності, її результативність, перспективи. Автори зазначають, що для того, щоб сформувати позитивну думку населення щодо професії, варто проводити просвітницьку роботу і формувати образ професії і фахівця (Staniforth, Deane, Kelsey, Beddoe, 2016). Крім того, імідж соціального працівника повинен включати турботу про людей, задоволення їхніх потреб, адже фахівець із соціальної роботи виступає джерелом допомоги для людей (Williams, Simon, Bell, 2015).…”
Section: результати та дискусіїunclassified
“…824-837. Staniforth, B., Deane, Kelsey L., & Beddoe, L. (2016). Comparing public perceptions of social work and social workers' expectations of the public view.…”
Section: висновкиmentioning
confidence: 99%
“…One reason for this is that many people may never have met a social worker, nor are social workers particularly visible in popular culture (Zugazaga, Surette, Mendez, & Otto, 2006 This study was conducted as part of a multi-phase data collection project focused on public perceptions of social work. Other reported phases included a phone survey on this subject (Staniforth, Fouché, & Beddoe, 2014) and an online survey on social workers' beliefs about public perceptions of social work (Beddoe, Staniforth, & Fouché, 2017;Staniforth, Deane, & Beddoe, 2016).…”
mentioning
confidence: 99%